Evaluating School-based Assessment (SBA): Primary School Teachers’ Perception and Practices in West Bengal - Das, Bipasha; Verma, Satyam; Gardia, Alok (THE PRIMARY TEACHER, 2025)
This descriptive survey study has been conducted to learn the perceptions of primary school teachers in West Bengal, India about School-based Assessment (SBA) and the approaches they employed to implement it. A survey of 118 teachers in Purba Bardhhaman district, West Bengal, India, was conducted, using a questionnaire to collect data. The results were analysed using inferential statistical analysis and non-parametric tests due to the abnormality of the dependent variable. According to the study, a Kruskal-Wallis H test revealed a statistically significant difference between the teacher’s perception of SBA and their educational qualifications. Also, the study found that the teaching experience of teachers makes a difference in implementing and adopting SBA practices in primary standard school curricula. Finally, this paper includes a brief discussion of the study’s findings, a few limitations and some suggestions for the future.